2020
DOI: 10.1101/2020.04.11.037101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional profiling and single-cell chimerism analysis identifies human tissue resident T cells in the human skin after allogeneic stem cell transplantation

Abstract: Tissue resident memory T cells (TRM) have recently emerged as crucial cellular players for host defense in a wide variety of tissues and barrier sites. Mouse models revealed that they are maintained long-term in loco unlike recirculating effector memory T cells (TEM). Insights into the maintenance and regulatory checkpoints of human tissue resident T cells (TRM) remain scarce, especially due to the obstacles in tracking T cells over time and system-wide in humans.We present a clinical model that allowed us to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…We also found increased expression of protein-coding genes for fatty acid–binding protein 5 ( FABP5 ) and LGALS3 , as well as the transcription factors RUNX3 and PRDM1 ( Fig. 5 E ), all previously described in TRMs ( de Almeida et al, 2020 Preprint ; Milner et al, 2017 ; Pan et al, 2017 ; Strobl et al, 2020b ). The majority of cells in this cluster expressed genes encoding for the αβ-TCR ( Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…We also found increased expression of protein-coding genes for fatty acid–binding protein 5 ( FABP5 ) and LGALS3 , as well as the transcription factors RUNX3 and PRDM1 ( Fig. 5 E ), all previously described in TRMs ( de Almeida et al, 2020 Preprint ; Milner et al, 2017 ; Pan et al, 2017 ; Strobl et al, 2020b ). The majority of cells in this cluster expressed genes encoding for the αβ-TCR ( Fig.…”
Section: Resultssupporting
confidence: 59%
“…4 E ). Interestingly, we found host cells to have a gene expression profile relating to a cTRM phenotype, with a trend of higher expression of cTRM markers ITGAE (CD103), SELPLG (encoding for CLA), LGALS3 (encoding for Galectin-3), and PRDM1 , which have been associated with TRMs ( de Almeida et al, 2020 Preprint ; Mackay et al, 2016 ; Strobl et al, 2020b ). Host cells also displayed significantly higher levels of FABP5 , encoding for the fatty acid–binding protein 5 known to be crucial for skin TRM metabolism ( Pan et al, 2017 ).…”
Section: Resultsmentioning
confidence: 95%
“…2C and Table 3B). This represents a proof of concept for the existence of a long-term bona fide skin-resident T cell subset (skin T RM ) (15).…”
Section: The Long-term Persistence Of Host Lymphocytes In the Skin Af...mentioning
confidence: 78%
“…The strength of this approach is that no additional sequencing is needed and that it allows for annotation of even rare cells through a simple but robust analysis. Examples include tracking of circulating host tissue-resident T cells following myeloablative conditioning ( 122 ) or donor-derived immune cells following solid organ transplant ( 123 ). A limitation is that sex mismatch only occurs in a subset of transplants.…”
Section: Lineage-tracing In the Context Of Allogeneic Stem Cell Transplantationmentioning
confidence: 99%
“…Lineage-tracing approaches have the potential to deepen the understanding of GvHD by dissecting the contribution of donor and recipient-derived T cells to GvHD target organs. An example of this approach demonstrated that tissue-resident memory T cells can retain a large fraction of host cells despite full systemic chimerism ( 122 ).…”
Section: Lineage-tracing In the Context Of Allogeneic Stem Cell Transplantationmentioning
confidence: 99%